Cloning and Functional Characterization of Key Enzymes in Putative Octadecanoid Pathway of Physcomitrella patens - P.K.G.S.S. Bandara (Tropical Agricultural Research, 2015)
Jasmonic acid and its metabolites are ubiquitously occurring lipid-derived signaling compounds that regulate growth, development and defense processes in flowering plants. However, their functions in lower land plants have not been well characterized yet. The model moss, Physcomitrella patens is a member of bryophytes and represents a key evolutionary position between green algae and flowering plants. According to the proposed land plant evolution, jasmonic acid signaling pathway has evolved after the evolutionary split of bryophytes and vascular plants, indicating its absence in bryophytes. However, the putative key homologous genes involved in jasmonic acid biosynthesis and its signaling pathway are available in P. patens genome. Allene oxide synthase catalyzes the first committed step of jasmonic acid biosynthesis in flowering plants. A putative allene oxide synthase gene of P. patens was cloned and shown to have the same in vitro function as observed in flowering plants. Moreover, based on substrate specificity, plant 12-oxophytodienoic acid reductases can be classified into two groups, group I and group II, of which only group II isozymes involve in jasmonic acid biosynthesis. Six putative 12-oxophytodienoic acid reductase genes, among which only one represents group II, were identified in P. patens genome. Two 12-oxo-phytodienoic acid reductase genes, which represent group I and group II, were cloned and characterized. Striking results were obtained since the 12-oxo-phytodienoic acid reductase, which represents group II, exhibited group I type activity. This unusual functional property clearly explains why P. patens, probably all the bryophytes, does not contain jasmonic and its signaling pathway though it contains the corresponding homologous genes. Moreover, the ancestral plant 12-oxophytodienoic acid reductases might have possessed group I type activity and early precursors of jasmonic acid might have functioned as signaling molecules in ancestral land plants instead of jasmonic acid. Tropical Agricultural Research Vol. 23 (2):160– 167 (2012)